Biomechanically designed Curve Specific Corrective Exercise for Adolescent Idiopathic Scoliosis gives significant outcomes in an Adult: A case report - Maharathi, Sujata; Iyengar, Raju; Chandrasekhar, Patnala (Frontiers in Rehabilitation Sciences, 2023)
Back ground-This study presents findings on improvements of Frontal and Sagittal Cobb angle, Global Spinal balance, and lung function parameters (FEV1, PEF) in an adult male with idiopathic scoliosis suffering from pain during ADL and sports activities and was treated with the biomechanically designed exercise protocol. Case Presentation-The 26-year-old male reported upper and middle back pain which aggravated during playing cricket. Whole spine standing X-Ray AP view revealed a right thoracic Scoliosis (Lenke 1 curve) of Cobb angle 48.6o with left lumbar compensatory curve of 24.7o, Thoracic hypo kyphosis of 9.9o, VAS rating for pain was 8. The patient was treated with myofascial release, stretching, aerobics, strengthening exercises, Breathing with core for stabilization and biomechanically designed curve specific corrective exercises. Results-Re-assessment 32 weeks post intervention demonstrated significant reduction in the major Cobb angle by 11.4o, minor Cobb angle by 10.5o, Thoracic hypokyphosis normalised to 37.8o, Coronal balance improved by 17.4 mm, Sagittal balance regained by 4.2 mm, Spine ROM improved by a total of 6.5 cm, Enhancement of pulmonary function of FEV1 by 7 % and PEF by 18 litres/min, dramatic improvement in aesthetics and pain perception. Conclusion-The biomechanically designed exercise protocol helped straighten the curve by corrective exercises and stabilized the curve by “Breathing with core”, treated the associated signs and symptoms of spinal pain by myofascial release and proper ergonomics, pulmonary dysfunction by aerobics, muscle tightness & weakness (due to altered length-tension) by stretching and strengthening.